Energy spectra and expectation values of selected diatomic molecules through the solutions of Klein–Gordon equation with Eckart–Hellmann potential model. (2nd December 2021) - Inyang, E. P.; William, E. S.; Obu, J. A.; Ita, B. I.; Inyang, E. P.; Akpan, I. O.
Abstract : We solved the Klein–Gordon equation using the Nikiforov–Uvarov (NU) method with Eckart–Hellmann potential (EHP) model with approximation to the centrifugal term. The analytical expression of the ro-vibrational energy spectra in relativistic, non-relativistic and the corresponding normalised wavefunction were obtained. The numerical bound states energy for various screening parameters at different quantum states and ro-vibrational energies of EHP for VH, TiH, NiC, TiC and CuLi diatomicmolecules were computed. We have also obtained the expectation values of r − 2, T and P 2 using Hellmann–Feynman theorem for the selected diatomic molecules. Graphically, we have illustrated the variation of ro-vibrational energies and expectation values of r − 2, T and P 2 . Four special cases of EHP where obtained and the results were in excellent agreements with the existing literature. GRAPHICAL ABSTRACT: UF0001